The Ozonation Process for Increasing Value Added Tallow of Cow as A Polyol - Yoshi, Linda Aliffia; Fitria, Nadya; Albana, Naufal Rozin; Enjarlis, Enjarlis; Wibawa, Agam Duma (INTEK: Jurnal Penelitian, 2020)
The purpose of this research is to produce polyol, through the ozonation process and to find the best catalysts and solvents for the formation of hydroxyl group. The hydroxyl group is indicator of the formation polyol. The process of making polyols is unsaturated fatty acids of the cow through the process of ozonation, using the solvents of sorbitol and glycerol, as well as catalysts of sulfuric acid and sodium hydroxide. The reaction temperature is run at 50oC and ozone levels are 4.33, 4.795, 5.021, 5.480 grams. The best results used a glycerol solvent, a sodium sulfate catalyst, and a 5.48 gram ozon content.